Structurally preserved fungi from Antarctica: diversity and interactions in late Palaeozoic and Mesozoic polar forest ecosystems. Issue 3 (18th March 2016) - Harper, Carla J.; Taylor, Thomas N.; Krings, Michael; Taylor, Edith L.
Abstract: Chert and silicified wood from the Permian through Cretaceous of Antarctica contain abundant information on fungal diversity and plant–fungal interactions. The chert deposits represent a particularly interesting setting for the study of plant–fungal interactions because they preserve remains of distinctive high latitude forest ecosystems with polar light regimes that underwent a profound climate change from icehouse to greenhouse conditions. Moreover, some of the cherts and wood show the predominance of extinct groups of seed plants (e.g. Glossopteridales, Corystospermales). Over the past 30 years, documentation of fossil fungi from Antarctica has shifted from a by-product of plant descriptive studies to a focused research effort. This paper critically reviews the published record of fungi and fungal associations and interactions in the late Palaeozoic and Mesozoic cherts and silicified wood from Antarctica; certain fungal palynomorphs and fungal remains associated with adpression fossils and cuticles are also considered. Evidence of mutualistic (mycorrhizal), parasitic and saprotrophic fungi associated with plant roots, stems, leaves and reproductive organs is presented, together with fungi occurring within the peat matrix and animal–fungus interactions. Special attention is paid to the morphology of the fungi, their systematic position and features that can be used to infer fungal nutritional modes.